Performance of high conformability vs. high radial force devices in the virtual treatment of TAVI patients with bicuspid aortic valve. (March 2021) - Finotello, Alice; Romarowski, Rodrigo M.; Gorla, Riccardo; Bianchi, Giovanni; Bedogni, Francesco; Auricchio, Ferdinando; Morganti, Simone
Highlights: Bicuspid aortic valve cases have been long contraindicated for TAVI. Patient-specific computational simulations of TAVI in bicuspid aortic valve anatomies are performed. High radial force devices vs high conformability devices are investigated. Four patient-specific clinical cases of bicuspid aortic valve are studied in details. High radial force is a more desired characteristic in a device that will be deployed in bicuspid valve patients. Abstract: Objective: Transcatheter Aortic Valve Implantation (TAVI) is a consolidated procedure showing a low operative risk and excellent long-term outcomes in patients with aortic stenosis. Patients presenting a bicuspid aortic valve (BAV) often require valve replacement due to the highly calcific nature of the aortic leaflets. However, BAV patients have usually been contraindicated for TAVI due to their complex valve anatomy. The aim of this work was to compare the performance of devices featuring high conformability (HC) against those with high radial force (HRF). Methods: Four BAV patients undergoing TAVI were retrospectively selected. The aortic roots including the native leaflets and calcifications were reconstructed from pre-operative Computed Tomography scans. In each patient, both HC and HRF devices were virtually implanted using Finite Element Analysis simulations. After implantation, paravalvular orifice area, von Mises stress distribution, root contact area, and device eccentricity were calculated. Results: Simulations showed good agreement with intraoperative imaging. In 3 out of 4 patients, the HRF device resulted in a lower paravalvular area than the HC. Stress distribution was also more homogeneously distributed in the HRF group as compared with the HC group. Despite their lower adaptability, HRF devices showed consistently higher stent-root contact area. Conclusion: HRF devices showed improved results with respect to HC valves after being deployed in BAV anatomies. We hypothesize that the ability to reshape the annulus is the major determinant of success in this subgroup of patients featuring highly calcified leaflets.